2012
DOI: 10.1002/jor.22276
|View full text |Cite
|
Sign up to set email alerts
|

Similar growth plate morphology in stapling and tension band plating hemiepiphysiodesis: A porcine experimental histomorphometric study

Abstract: The tension band plating technique for hemiepiphysiodesis is new and advocated because it is believed to reduce the risk of premature closure of the growth plate compared to stapling. The benefit of the tension band plating technique has not yet been proven in experimental or randomized clinical studies. Ten weeks old domestic pigs in two randomized, paired studies were used. Right proximal tibia was randomized to medial epiphysiodesis by either stapling or tension band plating. Left side received the opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…The choice was arbitrary, as the data available on the histological changes after hemiepiphysiodesis were limited. 18 Based on the literature, 19 we believed that three histological controls for each of the cut-off points would be sufficient for histological comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice was arbitrary, as the data available on the histological changes after hemiepiphysiodesis were limited. 18 Based on the literature, 19 we believed that three histological controls for each of the cut-off points would be sufficient for histological comparison.…”
Section: Methodsmentioning
confidence: 99%
“…A sham group was not used, as in previous studies of hemiepiphysiodesis no influence had been revealed. 18,20 The surgery comprised a medial proximal tibial hemiepiphysiodesis using a twohole titanium plate and screws (Normed, Tuttlingen, Germany). The device was left in place for three weeks and then removed.…”
Section: Methodsmentioning
confidence: 99%
“…Since its first description by Phemister in 1933, epiphysiodesis has become a common treatment for correction of deformities in growing children. Several techniques are currently used and all the non-reversible ones are used to obtain a permanent closure of the growth plate [3]. Thermal epiphysiodesis using radiofrequency ablation (RFA) has been reported as a successful treatment that can arrest growth in rabbits [46].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of RFA epiphysiodesis in large species have not yet been described, to our knowledge. The histology of two reversible methods has been studied previously [3]. Micro-characteristics are important, sometimes crucial, to understanding disease and treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation